2016
DOI: 10.1111/1365-2745.12534
|View full text |Cite
|
Sign up to set email alerts
|

Biotic resistance to tropical ornamental invasion

Abstract: Summary We examined invasive, casual (found occasionally outside cultivation) and non‐invasive (found only in cultivation) species to investigate the role of species traits and two forms of biotic resistance (plant neighbours and herbivores) in limiting invasion in Hawaiian lowlands. Seeds of 21 species of common woody ornamentals from three plant families (Acanthaceae, Apocynaceae, Bignoniaceae) that are non‐invasive, casual or invasive in Hawai'i were outplanted at two field sites. We measured germination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 85 publications
(126 reference statements)
1
17
0
Order By: Relevance
“…There is evidence that for several other woody plant species in Hawaii, biotic resistance through competition and herbivory (Bufford et al. ), and sterility or lack of pollinator services (Bufford and Daehler ), cause non‐native species to fail.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is evidence that for several other woody plant species in Hawaii, biotic resistance through competition and herbivory (Bufford et al. ), and sterility or lack of pollinator services (Bufford and Daehler ), cause non‐native species to fail.…”
Section: Discussionmentioning
confidence: 99%
“…Given that this species has not been able to successfully spread well beyond planting sites in Hawaii, despite being able to tolerate herbivory at early growth stages, there are likely other barriers to its invasion success. There is evidence that for several other woody plant species in Hawaii, biotic resistance through competition and herbivory (Bufford et al 2016), and sterility or lack of pollinator services (Bufford and Daehler 2014), cause non-native species to fail.…”
Section: Overcompensation In C Viminalismentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the factors that regulate community invasibility is critical for predicting and controlling plant invasions [3]. Prior studies have shown that successful plant invasions are related to the vegetation characteristics of recipient communities; these characteristics actually affect both the resource availability of habitats and biotic resistance [4][5][6][7][8]. For example, high species diversity sufficiently fills available niches and limits resource supply for invaders, while native species decrease establishment success of invader species that are similar to them in species traits (limiting similarity) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%